Mrs. Katz and Tush - Polacco, Patricia (Bantam Books, 1992)
A long-lasting friendship develops between Larnel, a young African-American, and Mrs. Katz, a lonely, Jewish widow, when Larnel presents Mrs. Katz with a scrawny kitten without a tail.